Gambaran Karakteristik dan Pengetahuan Ibu Mengenai Pemberian Imunisasi Dasae Lengkap Pada Bayi Usia 0-12 Bulan di Wilayah Kerja Puskesmas Medono Koya Pekalongan - Wahani, Salisa Tara; Mustikawati, Neti (Universitas Malahayati, 2023)
ABSTRACT The coverage of complete basic immunization in Pekalongan City in 2021 was 86.06% out of 5110. This number did not meet the 2021 Strategic Plan target of 93.6%. This study aims to describe maternal knowledge regarding the administration of complete basic immunization for infants aged 0-12 months. This quantitative descriptive research design involved 45 mothers with infants aged 1 month in the working area of Medono Community Health Center. Total sampling technique was used. Data analysis of characteristics was conducted using univariate analysis, while knowledge was analysed using frequency and percentage. The results showed that the mean age of the respondents was 30 years, and they had an average of 2 children. 23 respondents (51.1%) had completed high school education, and 27 (60%) were not employed. 24 respondents (53.3%) had previous experience. All 45 respondents (100%) were Muslims and of Javanese ethnicity. The description of maternal knowledge regarding the administration of complete basic immunization for infants aged 0-12 months indicated that the majority of respondents had a category of insufficient knowledge (60%), a moderate knowledge category had 15 respondents (33.3%), and only 3 respondents (6.7%) had a good knowledge category. The majority of respondents had insufficient knowledge, indicating aneed for education using media-printed, posters, and brochures. Keywords: Demographic Characteristics, Immunization, Knowledge ABSTRAK Cakupan imunisasi dasar lengkap di Kota Pekalongan tahun 2021 86,06% dari 5110. Angkanya belum memenuhi target Renstra tahun 2021 yaitu 93,6%. Penelitian ini bertujuan untuk mendeskripsikan gambaran pengetahuan ibu mengenai pemberian imunisasi dasar lengkap pada bayi usia 0-12. Desain penelitian kuantitatif deskriptif dengan 45 ibu yang mempunyai bayi usia 1 bulan di wilayah kerja Puskesmas Medono. Teknik total sampling. Analisa data karakteristik menggunakan univariat dan pengetahuan dianalisa dengan frekuensi dan presentase. Hasil penelitian karakteristik responden rata rata berusia 30 tahun dan mempunyai 2 anak, responden berpendidikan SMA/SMK 23 (51,1%), 27 (60%) tidak bekerja, responden yang berpengalaman 24 (53,3%), seluruh responden 45 (100%) beragama islam dan suku jawa. Gambaran pengetahuan ibu mengenai pemberian imunisasi dasar lengkap pada bayi usia 0-12 bulan sebagian besar responden kategori pengetahuan kurang 27 (60%), di kategori pengetahuan yang cukup ada 15 (33,3%), dan kategori pengetahuan baik hanya 3 (6,7%). Sebagian besar responden memiliki pengetahuan yang kurang sehingga perlu dilakukan penyuluhan dengan menggunakan media cetak, poster, dan brosur. Kata Kunci: Karakteristik Demografi, Pengetahuan, Imunisasi